A Simple Colorimetric Detection of Bisphenol A in Exposed Drinking Bottles Using a Paper-Based Sensor - Ganjar Fadillah; Agung Guritno; Akhmarin Rista Ashri; Putri Fahria Lesmana; Fatmawati Fatmawati; Gus Nizar Zahardin; Nur Apriyani (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2025)
Bisphenol-A (BPA) is a chemical widely used in the production of polycarbonate plastics and epoxy resins, commonly found in bottled water containers. BPA migration into drinking water can occur due to variations in pH and temperature during storage, posing potential health risks with prolonged exposure. This study focuses on the development of a rapid and accurate colorimetric paper sensor for BPA detection. The sensor employs a chromogenic reagent that selectively reacts with BPA, resulting in a visible color change from yellow to dark red. Experimental results demonstrated that the sensor exhibits high sensitivity, with a limit of detection (LOD) of approximately 0.29 mmol L⁻¹. Validation using water samples from plastic bottles exposed to environmental conditions confirmed the sensor’s capability to effectively identify BPA leaching. Additionally, the sensor showed excellent stability, indicated by a relative standard deviation (%RSD) of 0.62%, and high accuracy, with recovery values ranging from 100.87% to 107.39%. These findings suggest that the developed colorimetric paper sensor is a promising tool for on-site monitoring of BPA contamination in drinking water, providing a simple, fast, and cost-effective alternative to conventional analytical methods.